PERSEPSI PENGUNJUNG TERHADAP BUAYA MUARA (Crocodylus porosus) DAN FASILITAS PEMELIHARAAN DI PENANGKARAN DAN KEBUN BINATANG - Vidya Elza Loriza; Mirza Dikari Kusrini; Resti Meilani (Scripta Biologica, 2019)
Estuarine crocodile often considered as dangerous animal due to continual news of human crocodile conflict cases around the world.  This study aimed to analyze the perception of visitors about estuarine crocodile in captivity and facilities in two captive breeding sites. We conducted field observation and structured interview to 120 respondents in two local zoos: the Indonesia Jaya Crocodile Park (TBIJ or crocodile park)  in Bekasi and Ragunan Zoo (TMR or the zoo) in Jakarta. All visitors have low knowledge about estuarine crocodile, which they obtained mostly from mass media. Although most visitors know that estuarine crocodies are protected however in pratice their don’t have enough empathy to captive crocodiles. Visitors to both areas are local who lives near the vicinity of the park or zoo. Crocodile park visitors mostly came from Bekasi with an average number of visits 1 time and 1-hour length of visit. The reason for their visit were the closeness of the location and to learn crocodiles. The zoo visitors mostly came from Jakarta with an average number of visits more than 3 times and 6 hours length of visits. Respondents visited the zoo because of low cost and recreation. Visitors of the zoo provided  positive review for several aspects in the zoo, while visitors in crocodile park gave positive review only on physical condition of crocodiles.